2015
DOI: 10.2172/1214539
|View full text |Cite
|
Sign up to set email alerts
|

RHIC operation with asymmetric collisions in 2015

Abstract: To study low-x shadowing/saturation physics as well as other nuclear effects [1, 2], proton-gold (p-Au, for 5 weeks) and proton-Aluminum (p-Al, for 2 weeks) collisions were provided for experiments in 2015 at the Relativistic Heavy Ion Collider (RHIC), with polarized proton beam in the Blue ring and Au/Al beam in the Yellow ring. The special features of the asymmetric run in 2015 will be introduced. The operation experience will be reviewed as well in the report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In part of Run 15 the yellow ring was filled with 100 GeV/n Au and Al nuclei [10]. It was found that time/amplitude distributions ( Fig.…”
Section: Analyzing Power For P ↑ a Elastic Scatteringmentioning
confidence: 94%
“…In part of Run 15 the yellow ring was filled with 100 GeV/n Au and Al nuclei [10]. It was found that time/amplitude distributions ( Fig.…”
Section: Analyzing Power For P ↑ a Elastic Scatteringmentioning
confidence: 94%
“…During the p þ Al operation, there was a 3.25 mrad crossing angle offset and a 16.2 mm position offset in the horizontal plane because of the asymmetric beams [47]. Therefore, the electron beam position and angle needed to be moved closer to the ion beam first.…”
Section: Beam-beam Experimentsmentioning
confidence: 99%
“…The deuteron intensity was limited at transition crossing in RHIC as well. The deuteron beam is accelerated to top energy with the revolution frequency locked with that of the gold beam [8]. Therefore, it crosses transition energy at a time slightly different from the gold beam due to path length difference of them.…”
Section: Beam Intensitymentioning
confidence: 99%